Sumber Nilai Dalam Demokrasi Desa: Telaah Literatur Terhadap Prinsip-Prinsip Partisipasi Dan Kearifan Lokal - Sesilia Viktoria Harefa (CV. SINAR HOWUHOWU, 2025)
Village democracy is a tangible form of governance at the grassroots level that embodies direct community involvement in decision-making. In the Indonesian context, village democracy is shaped not only by formal regulations, but also influenced by local values that exist in the community. This article seeks to explore the value bases that underpin village democracy by reviewing the literature on principles of participation and local knowledge. The research employs a descriptive qualitative strategy using a literature review method based on a wide array of scholarly literature and government policies. The findings show that village democracy is based on the principles of citizen engagement, collective deliberation, collaborative efforts, and respect for local knowledge. These values serve as the foundation for building inclusive, accountable, and sustainable village governance. Thus, village democracy not only functions as a political mechanism, but also as a tool to maintain the cultural values inherent in the community.